Розвиток наукових уявлень про зловживання правом у вітчизняній юриспруденції - Гуртова, К. М.; Hurtova, K. M.; Ксенія Гуртова (Вісник Харківського національного університету внутрішніх справ. – 2023. – № 4 (103). - С. 315-323, 2023)
Визначено, що зловживання правом є однією з найважливіших проблем сучасної юридичної науки, а також складною та контроверсійною правовою категорією. Дослідження вказаної проблематики має як теоретичний, так і прикладний інтерес для розвитку вітчизняної правової науки. Проаналізовано основні наявні у вітчизняній науці та історичних джерелах підходи до трактування дефініції «зловживання правом», основні ознаки зловживання правом як здійснення суб’єктивного права, що завдає шкоди іншій особі й може вступати в суперечність із совістю та моральними нормами особи.

The article defines the abuse of law as one of the most important problems of modern legal science, as well as a complex and controversial legal category, the relevance of which is directly related to the level of development of democracy, stability in the state and society, traditions of law-abiding and strict observance of human and citizen rights, research which have both theoretical and applied interest for the development of domestic legal science. The main approaches to the interpretation of the definition of “abuse of law” available in national science and historical sources are analysed, and the main features of abuse of law as the exercise of a subjective right which causes harm to another person and may contradict his/her conscience and moral standards are identified. In a retrospective perspective, an analysis of the development of scientific ideas cientific concepts on abuse of law in national jurisprudence in the pre-Soviet and Soviet periods has been carried out. In addition, normative legal documents that determined the specifics of law enforcement of this category during the formation of domestic law have been considered. It is noted that since the end of the 19th century, the problem of abuse of law has been considered as a question of the limits of behaviour of a subject exercising a subjective right granted by law. It is concluded that since this period, legal scholars and legislators have focused on the study of the need to prohibit the abuse of law at the legislative level. The article demonstrates that the establishment of the prohibition of abuse of law through appropriation of subjective rights was inherent in Soviet civil law with the simultaneous absence of clear signs of this legal concept at the legislative level throughout the Soviet period, and also the widespread view that the use of the term “abuse of law” should be conditional and require a clear distinction between it and the implementation of law.

Определено, что злоупотребление правом является одной из важнейших проблем современной юридической науки, а также сложной и контроверсионной правовой категорией. Исследование указанной проблематики имеет как теоретический, так и прикладной интерес для развития отечественной правовой науки. Проанализированы основные имеющиеся в отечественной науке и исторических источниках подходы к трактовке дефиниции «злоупотребление правом», основные признаки злоупотребления правом как осуществление субъективного права, наносящего вред другому лицу может вступать в противоречие с совестью и моральными нормами личности.
Development of scientific concepts on abuse of law in national jurisprudence
Keywords: зловживання правом; правопорушення; шикана; суб’єктивне право; суддівський розсуд; abuse of law; offense; chicanery; subjective law; judicial discretion; злоупотребление правом; правонарушение; субъективное право; судейское усмотрение